1999
DOI: 10.1192/bjp.175.4.317
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of admission to a medium secure psychiatric unit

Abstract: The higher rate of admission of African-Caribbean patients is consistent with a higher level of demand. There is a need for studies of the pathways by which patients from ethnic minorities reach medium-security accommodation, with a view to early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
72
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 15 publications
8
72
1
Order By: Relevance
“…That study also found that 50 former patients (21%) spent some of the follow-up period in a high secure hospital, including 27 patients discharged directly to such hospitals. 6 A high rate of readmission to any hospital was also shown in another, albeit smaller, medium secure unit cohort of 63 former patients with schizophrenia, with 56 (89%) patients requiring at least one readmission to a psychiatric hospital (mean follow-up 5.4 years), of whom 41 (73%) had multiple readmissions. 7 A large survey of all medium secure units in England and Wales found a readmission rate of 27% for women and 21% for men within 1 year.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…That study also found that 50 former patients (21%) spent some of the follow-up period in a high secure hospital, including 27 patients discharged directly to such hospitals. 6 A high rate of readmission to any hospital was also shown in another, albeit smaller, medium secure unit cohort of 63 former patients with schizophrenia, with 56 (89%) patients requiring at least one readmission to a psychiatric hospital (mean follow-up 5.4 years), of whom 41 (73%) had multiple readmissions. 7 A large survey of all medium secure units in England and Wales found a readmission rate of 27% for women and 21% for men within 1 year.…”
mentioning
confidence: 72%
“…6 Other variables such as age, gender and number of convictions were not associated with readmission. That study also found that 50 former patients (21%) spent some of the follow-up period in a high secure hospital, including 27 patients discharged directly to such hospitals.…”
mentioning
confidence: 92%
“…Despite the availability of many descriptive studies on psychiatric hospitalizations [11][12][13][14][15][16][17][18] few have worked with large and representative samples collected from large regions involving more than one hospitalization unit, [19][20][21] thus providing a more encompassing view of the mental health network.…”
Section: Discussionmentioning
confidence: 99%
“…In several Western countries, the average duration a patient stays in highly secure forensic settings has been rising (Andreasson et al, 2014;Davoren et al, 2012;Margetić, Margetić, & Ivanec, 2014;O'Neill et al, 2003;Ross, Querengässer, Fontao, & Hoffmann, 2012;Shah, Waldron, Boast, Coid, & Ullrich, 2011;Sharma et al, 2015). Two decades ago researchers in the UK reported mean LOS in medium security was less than 2 years (Maden, Friendship, McClintock, & Rutter, 1999;McKenna, 1996). In 2002, a UK study showed that mean LOS exceeds 5 years for about 10% of forensic psychiatric patients (Edwards, Steed, & Murray, 2002).…”
Section: Introductionmentioning
confidence: 99%